2016
DOI: 10.1259/bjr.20160522
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of integrated total pelvic floor ultrasound compared to defaecatory MRI in females with pelvic floor defaecatory dysfunction

Abstract: Cite this article as:Hainsworth AJ, Pilkington SA, Grierson C, Rutherford E, Schizas AMP, Nugent KP, et al. Accuracy of integrated total pelvic floor ultrasound compared to defaecatory MRI in females with pelvic floor defaecatory dysfunction. Objective: Defaecatory MRI allows multicompartmental assessment of defaecatory dysfunction but is often inaccessible. Integrated total pelvic floor ultrasound (transperineal, transvaginal, endoanal) may provide a cheap, portable alternative. The accuracy of total pelvic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…The accuracy of total pelvic floor ultrasound for anatomical abnormalities when compared with defecatory MRI was assessed by Hainsworth at al. (14). They found that sensitivity and specificity of total pelvic floor ultrasound were 81% and 33% for rectocele, 60% and 91% for intussusception, 65% and 80% for enterocele and 65% and 84% for cystocele when compared with defecatory MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of total pelvic floor ultrasound for anatomical abnormalities when compared with defecatory MRI was assessed by Hainsworth at al. (14). They found that sensitivity and specificity of total pelvic floor ultrasound were 81% and 33% for rectocele, 60% and 91% for intussusception, 65% and 80% for enterocele and 65% and 84% for cystocele when compared with defecatory MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of transvaginal as well as trans abdominal sonographic is within clinically acceptable limits 23 . With the developments of the machines and introduction of the high-resolution transducer in state of the art modalities, improved the accuracy of ultrasound in the measurement of endometrium 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Imaging plays an important role to go beyond imagination. It provides a better understanding of the pathophysiology of PFD, visualizing abnormalities undetected by the clinicians and/or confirming clinical findings to correlate with symptoms [12][13][14][15]. Although, in recent years, new techniques have been dramatically improved the diagnostic accuracy in patients with PFD, there is still no single modality than can provide a comprehensive overview of the PF.…”
mentioning
confidence: 99%
“…They found no superiority of 4D over dynamic 2D US and concluded that these two techniques could be used interchangeably to screen women with ODS. Hainsworth et al [14] compared the accuracy of integrated total PFUS (transperineal, transvaginal, endoanal) to defaecatory MR. The results supported the use of integrated US as a screening tool for defaecatory dysfunction.…”
mentioning
confidence: 99%